THE EFFECT OF CHRONIC POLYPHARMACY, THE DRUG BURDEN INDEX (DBI) AND DEPRESCRIBING ON PHYSICAL FUNCTION IN AGED MICE. (11th November 2018) - Mach, J; Gemikonakli, G; Kane, A; Howlett, S; deCabo, R; Le Couteur, D; Hilmer, S
Abstract: Polypharmacy (use of ≥ 5 drugs) and increasing DBI (measure of total exposure to anticholinergic and sedative drugs) is associated with impaired physical function in observational studies of older adults. We aim to determine the effect of polypharmacy, DBI and deprescribing (withdrawing drugs) on functional outcomes in aged mice. From 12 to 21 months of age male C57BL/6 mice were fed control or treatment containing therapeutic doses of five drugs with Zero DBI (simvastatin, metoprolol, omeprazole, paracetamol, irbesartan), Low DBI (simvastatin, metoprolol, omeprazole, paracetamol, citalopram), High DBI (simvastatin, metoprolol, oxybutynin, oxycodone, citalopram), or single drug (simvastatin, metoprolol, oxybutynin, oxycodone or citalopram) (n=40/ group). At 21 months, animals either continued treatment or were deprescribed (n=20/ group). Functional tests were conducted at 12, 15, 18, 21 and 24 months. From 12–24 months, compared to control diet, locomotor activity (open field) and nest making declined following Low DBI, High DBI and citalopram treatment, frailty index score increased following High and citalopram treatment, and grip strength (wire hang) decreased following Low DBI and citalopram treatment (p<0.05). Deprescribing improved locomotor and nesting activity for Low DBI, High DBI and citalopram treatment and grip strength for Low DBI animals. Compared to control, a decline in muscle endurance (rotarod) was observed following citalopram treatment and was improved with deprescribing (p<0.05). Our results show for the first time in a preclinical model that chronic polypharmacy with increasing DBI or individual sedative or anticholinergic drugs impair function, which may be reversed with deprescribing. Future studies will investigate the mechanism.